Legal Responsibility for Corporations Against Environmental Damage Crimes - Sueni, Annisa Sabilla; S., Eko (DE LEGA LATA: JURNAL ILMU HUKUM, 2023)
The rise of the issue of environmental damage in various regions in Indonesia is a separate concern and problem for the relevant government to handle and overcome environmental issues, especially crimes committed by corporations. Where environmental damage is carried out by irresponsible corporations, and there is no re-treatment, so that nature in Indonesia is completely eroded and even becomes pollution and problems for the surrounding community. The method of writing this thesis uses a normative research method, namely legal research that puts the law as a building system for existing norms such as books, journals, and other references. Overall corporate responsibility for environmental crimes that exist in Indonesia, in terms of solving these problems, which is seen from the point of view of the laws and regulations governing it, both Law No. 03 of 2020 concerning Minerba, Law No. 32 of 2009 on the environment . In terms of minimizing corporate crime in the future, the author argues that it is mandatory to stipulate provisions regarding Residiv for the same perpetrators in terms of corporate crimes, the application of the principle of guilt in Islam (meaning who commits it is the one who must be responsible even though it is a legal entity), and commit Comparison with regulations regarding the environment and mining from other countries is assessed from the context of legal protection for victims (Compensation, Compensation, or Restitution).